Inhibition of Notch1 signaling promotes neuronal differentiation and improves functional recovery in spinal cord injury through suppressing the activation of Ras homolog family member A. Issue 6 (26th August 2019) - Peng, Zhiming; Li, Xiang; Fu, Mengxia; Zhu, Kai; Long, Lingli; Zhao, Xiaoyang; Chen, Qingui; Deng, David Y. B.; Wan, Yong
Abstract: Neural stem cells (NSCs) transplantation represents a promising strategy for the repair of injured neurons, since NSCs not only produce multiple neurotrophic growth factors but also differentiate into mature cells to replace damaged cells. Previous studies have shown that Notch signaling pathway had negative effects on neuronal differentiation; however, the precise mechanism remained inadequately understood. This research aimed to investigate whether inhibition of Notch1 signaling promotes neuronal differentiation and improves functional recovery in rat spinal cord injury through suppressing the activation of Ras homolog family member A (RhoA). QPCR, western blot, and immunofluorescence experiments were used to analyze Notch1 signaling pathways, RhoA, Ras homologous ‐associated coiled‐coil containing protein kinase 1 (ROCK1), cleaved caspased‐3, and neuronal/astrocytic differentiation markers. The expression of RhoA and ROCK1 was inhibited by lentivirus or specific biochemical inhibitors. In spinal cord injury (SCI), motor function was assessed by hind limbs movements and electrophysiology. Tissue repairing was measured by immunofluorescence, Nissl staining, Fluorogold, HE staining, QPCR, western blot, and magnetic resonance imaging (MRI) experiments. Our results demonstrate that inhibition of Notch1 in NSCs can promote the differentiation of NSCs to neurons. Knockdown of RhoA and inhibition of ROCK1 both can promote neuronal differentiation through inhibiting the activation of Notch1 signaling pathway in NSCs. In SCI, silencing RhoA enhanced neuronal differentiation and improved tissue repairing/functional recovery by inhibiting the activation of Notch1 signaling pathway. Since Notch1 inhibits neuronal differentiation through activating the RhoA/ROCK1 signaling pathway in NSCs, our data suggest that the Notch1/RhoA/ROCK1/Hes1/Hes5 signaling pathway may serve as a novel target for the treatment of SCI. Abstract : Notch1 and RhoA signaling pathway had negative effects on neuronal differentiation, however, their interaction remained unclear. We found that inhibition of Notch1 could decrease Hes1 and Hes5 through down‐regulating RhoA/ROCK1 to promote neuronal differentiation in neural stem cells. Our data suggest that Notch1/RhoA signaling pathway serves as a novel target for the treatment of spinal cord injury.